Molecular analysis of fine-needle aspiration cytology in thyroid disease: where are we?. Issue 2 (April 2021) - Grani, Giorgio; Sponziello, Marialuisa; Filetti, Sebastiano; Durante, Cosimo
Abstract : Purpose of review: The prevalence of thyroid nodules in the general population is high but only about 5% are malignant lesions. Cytology is usually appropriate to rule out malignancy in sonographically suspicious nodules but in many cases, reports are indeterminate. Molecular testing is a more recent approach to rule out malignancy and guide subsequent management. Recent findings: Although several different molecular testing approaches have proven useful in reducing unnecessary surgery, there are still several remaining issues, such as the possible occurrence of RAS mutations (which are difficult to interpret in clinical management) and the role of molecular analysis in specific histotypes, such as Hürthle cell carcinomas. Furthermore, conclusive evidence is lacking regarding the cost-effectiveness and appropriateness of surgical options following molecular tests. Summary: To be useful in clinical practice, molecular tests should be applied to appropriate candidates. In truly uncertain thyroid nodules in which diagnostic surgery may be considered, molecular testing may change the clinical approach and 'save' a number of thyroids.